Polar microalgae-based nanoparticles: a next-generation strategy for cancer treatment - Karaca, Gulcan Aysin; Erkin, Ozgur Cem; Inan, Benan; Balkanli, Didem (SPRINGER HEIDELBERG, 2025)
Polar microalgae are one of the species that produce valuable bioactives and effective antioxidants as a metabolic adaptation mechanism to tolerate harsh conditions of polar regions. In this manner, evaluating bioactive compounds obtained from polar microalgae against cancer cells is expected to offer promising outcomes. Among these bioactive compounds, the flavonoids found in microalgae stand out with their anticancer activity. In this study, flavonoid-rich extracts of Auxenochlorella pyrenoidosa Ozcimen.001 (CP) and Chlorella sorokiniana Egemen.002 (CS) isolated from polar regions and their encapsulated forms were investigated for their efficacy on A-549 and MCF-7 cell lines, respectively. The flavonoid contents of CP and CS extracts were found to be 1.16 mg Q/g DE and 0.6 mg Q/g DE, respectively. Both flavonoid-rich polar microalgae extracts (FRME) and nanoparticles loaded with these extracts (FRME-NP), which have a size range of 156-294 nm and 85-92% encapsulation efficiency, exhibited anti-cancer activity at various levels against A-549 and MCF-7 cell lines. In comparison with the A-549 cell line, CP and CS extracts in 100 mu g/mL concentration showed better results by decreasing the cell viability of MCF-7 to approximately 60% in 48 h. It has been determined that the longer the exposure time of cells to samples, the greater the decrease in cell viability. The data obtained from this study showed that polar microalgae have the potential to be evaluated as an anticarcinogenic agent in the pharmaceutical area. This context provides additional research and treatment perspectives that will support the development of novel biotechnological drugs for cancer treatment.
Keywords: Anti-cancer activity; C. pyrenoidosa; C. sorokiniana; Nanoparticle; Polar microalgae; FRESH-WATER MICROALGA; ANTICANCER; INFLAMMATION; FLAVONOIDS; Biotechnology & Applied Microbiology